Native plant bioaccumulation strategies: a baseline study for biomonitoring the Atlantic Forest. (30th June 2010) - Franca, Elvis J.; Fernandes, Elisabete A. De Nadai; Bacchi, Marcio A.; Rodrigues, Ricardo R.; Bode, Peter; Saiki, Mitiko
The atmosphere may act as an important source of chemical elements for the Atlantic Forest, one of the hottest world biodiversity hotspots. However, chemical responses for chemical element availability are not expected to be equal for each plant species. In this sense, the present work encompasses a baseline study for biomonitoring purposes based on the identification of different strategies of native tree species in accumulating chemical elements. Instrumental neutron activation analysis was employed for chemical characterisation of leaf and soil compartments. Results indicated a low level of pollution because the major part of the studied species has shown chemical mass fractions within the expected range in leaf compartment. By estimating leaf?soil bioaccumulation factor, some species were found to accumulate the nutrients Co, Na, Se and Zn, some trace elements Br, Ba, Cs, Hg, Rb, Sc and Sr and the lanthanides Ce, La and Sm despite the environmental variability.